Normal Variants and Pitfalls of 18F-FDG PET/CT Imaging in Pediatric Oncology - Purbhoo, Khushica; Vangu, Mboyo Di-Tamba (Frontiers in Nuclear Medicine, 2022)
Positron emission tomography (PET) with 2-[fluorine-18] fluoro-2- deoxy-D-glucose (FDG) is a well-established modality that is used in adult oncologic imaging. It is increasingly being used in paediatric oncology. The combination of functional and morphologic imaging in a combined PET/CT improves the diagnostic accuracy and thus the patient management. However, the clinician should be aware that the normal distribution of FDG uptake in children may differ from adults. Also, even though FDG is used widely in oncology, it is not tumour specific. Uptake of FDG may be seen in benign conditions, including trauma, infection and inflammation. Proper interpretation of paediatric FDG PET/CT studies requires knowledge of the normal distribution of FDG uptake in children, and at the same time, an insight into physiologic variants, benign lesions, and PET/CT related artefacts. Knowing these potential causes of misinterpretation can increase the accuracy of image interpretation, decrease the number of unnecessary follow-up studies or procedures, improve treatment and more importantly, reduce the radiation exposure to the patient. In this article, we review and discuss the normal distribution of FDG uptake in children, the physiological variants in distribution, benign lesions that could be misinterpreted as malignancy, and the common artefacts associated with PET/CT performed in paediatric oncology patients. We add a pictorial illustration to prompt understanding and familiarity with the above-mentioned patterns. Therefore, we believe that this review will assist in reducing possible mistakes by reading physicians and preventing incorrect interpretation.